2015
DOI: 10.1186/s12960-015-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles and competencies of district and sub-district pharmacists: a case study from Cape Town

Abstract: BackgroundDistrict and sub-district pharmacist positions were created during health sector reform in South Africa. High prevalence of HIV/AIDS, tuberculosis and increasing chronic non-communicable diseases have drawn attention to their pivotal roles in improving accessibility and appropriate use of medicines at the primary level. This research describes new roles and related competencies of district and sub-district pharmacists in Cape Town.MethodsBetween 2008 and 2011, the author (HB) conducted participatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…This runs against obvious gains experienced in health outcomes engendered by the participation of community pharmacists in other climes such as the United States, 30 United Kingdom, 31 Australia, 32 and South Africa. 33,34 The findings of the survey agree with the positions of key informants particularly in the under-explored potentials of community pharmacists for immunization services. The evidence equally underscore the claim that community pharmacy clients are getting more sophisticated such that a significant gap exists between customer expectations and service fulfilment (t = 14.59, P = .001).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This runs against obvious gains experienced in health outcomes engendered by the participation of community pharmacists in other climes such as the United States, 30 United Kingdom, 31 Australia, 32 and South Africa. 33,34 The findings of the survey agree with the positions of key informants particularly in the under-explored potentials of community pharmacists for immunization services. The evidence equally underscore the claim that community pharmacy clients are getting more sophisticated such that a significant gap exists between customer expectations and service fulfilment (t = 14.59, P = .001).…”
Section: Discussionsupporting
confidence: 68%
“…38 Recent evidence from South Africa also shows a shift to a multidisciplinary team approach. 33,34 In Nigeria however, the study found a lack of team approach to patient care with most community pharmacies operating as 'silos. ' About 80% (258) of the pharmacists either agreed or strongly agreed that this was a significant challenge, as corroborated by an Australian study.…”
Section: Adoption Of Technology For Primary Healthcare Services In Comentioning
confidence: 99%
“…Forbes T. et al (2004) carried out a survey of experts in Scotland and found that many doctors have decided to perform the duties of a manager to "protect their profession from influence by unauthorized persons or those they consider as inappropriate persons for the role of the healthcare leader" (36). Similar results were obtained in a survey of experts in Norway (37,38). According to Edmonstone J.…”
Section: Literature Reviewsupporting
confidence: 86%
“…In particular, Norway is one of the countries where this category of health care workers directly compete with doctors for management positions. According to Johansen and Gjerberg (2009), Norwegian nurses occupy management positions to improve their professional status (38). This fact confirms the sociological theory, according to which the post of the manager is seen as a tool to strengthen the position in the main profession.…”
Section: Literature Reviewmentioning
confidence: 82%
“…To address critical leadership, management and governance skill gaps in South Africa [ 47 ], the program applied the Pharmaceutical Leadership Development Program (PLDP). The PLDP brings together health care professionals, including clinicians, pharmacists, facility managers, and operational managers, to strengthen their leadership, management, and governance skills, while engaging them in analyzing a persistent challenge they face at the health facility they serve.…”
Section: Resultsmentioning
confidence: 99%